Coordination of Monetary and Fiscal Policies. (IMF Working Papers; Working Paper ;, 1998)
Recently, monetary authorities have increasingly focused on implementing policies to ensure price stability and strengthen central bank independence. Simultaneously, in the fiscal area, market development has allowed public debt managers to focus more on cost minimization. This 'divorce' of monetary and debt management functions in no way lessens the need for effective coordination of monetary and fiscal policy if overall economic performance is to be optimized and maintained in the long term. This paper analyzes these issues based on a review of the relevant literature and of country experiences from an institutional and operational perspective.